Bone Mineral Density among adolescent’s patients with β-thalassemia major. - Abbas Jaffri, Samar; Syed Muhammad Irfan; Sultana, Sadia; Syed Muhammad Usman; Nadeem, Sheeza (International Journal of Endorsing Health Science Research, 2021)
Background: Beta-thalassemia is an autosomal recessive hemoglobinopathy with frequent skeletal complications, often debilitating in adolescent patients. We aim to evaluate the bone mineral density (BMD) by dual-energy x-ray absorptiometry (DEXA) and ascertain osteoporosis/osteopenia frequency in patients with β-thalassemia major. Methodology: In this cross-sectional study, 36 adolescent patients with β-thalassemia major were enrolled from June 2015 to March 2017. BMD was measured in the anteroposterior lumbar spine (L1-L4) and femoral neck by DEXA. For the biochemical estimations, blood and urine samples were obtained and analyzed. The results of a bone density test were presented as T and Z scores. Results: There were 20 male and 16 female patients with a mean age of 21.33 ± 3.7 years. The mean bone mineral content (BMC) was 20.10 ± 6.0 gm, and the mean BMD was 0.65 ± 0.07 gm/cm2. The mean T score was -3.17 ± 1.04, and the Z score was -3.06 ± 1.06. All patients had low BMD, as depicted by their T or Z scores. The reported frequency of osteoporosis and osteopenia was 77.7% and 22.2%, respectively. Conclusion: All Beta-thalassemia major patients had low BMD with a remarkable incidence of osteoporosis. It is recommended to perform an annual BMD among thalassemic patients to prevent fatal consequences and achieve an optimal bone density among such patients.